Pulmonary Arterial Hypertension in a Patient with Cowden Syndrome and the PTEN Mutation. (1st December 2014) - Ha, Duc; Mester, Jessica; Eng, Charis; Farha, Samar
Abstract : The pathogenesis of pulmonary arterial hypertension (PAH) exhibits many neoplastic‐like features. Cowden syndrome is a difficult‐to‐recognize heritable cancer syndrome caused by a germline mutation in the phosphatase‐and‐tensin homolog deleted on the chromosome 10 ( PTEN ) gene. PTEN regulation has been implicated in cancer development and, more recently, PAH pathogenesis. Here we report a case of PAH in a patient with Cowden syndrome and the response to pulmonary vasodilators.